2007
DOI: 10.1107/s1744309107020313
|View full text |Cite
|
Sign up to set email alerts
|

Expression, crystallization and preliminary X-ray diffraction studies of recombinantClostridium perfringensβ2-toxin

Abstract: Clostridium perfringens is a Gram-positive sporulating anaerobic bacterium that is responsible for a wide spectrum of diseases in animals, birds and humans. The virulence of C. perfringens is associated with the production of several enterotoxins and exotoxins. beta2-toxin is a 28 kDa exotoxin produced by C. perfringens. It is implicated in necrotic enteritis in animals and humans, a disease characterized by a sudden acute onset with lethal hemorrhagic mucosal ulceration. The recombinant expression, purificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…That toxin was then crystallized using the batch-under-oil technique. Crystallographic analysis of this CPB2 crystal showed that the triangular prism shaped crystals measuring 200 microns belonged to primitive rhombohedral space group R3 , diffracting up to 2.9 Å [166]. …”
Section: Iota Toxinmentioning
confidence: 99%
“…That toxin was then crystallized using the batch-under-oil technique. Crystallographic analysis of this CPB2 crystal showed that the triangular prism shaped crystals measuring 200 microns belonged to primitive rhombohedral space group R3 , diffracting up to 2.9 Å [166]. …”
Section: Iota Toxinmentioning
confidence: 99%
“…Further studies demonstrated the in vitro cytotoxicity of the native CPB2 toxin in different intestinal cell lines; however, currently, its exact role in pathogenesis remains unclear [ 13 , 15 20 ]. In the last decades, many studies have been focused on the use of purified recombinant consensus CPB2 expressed in prokaryotic systems for immunological and crystallographic studies [ 21 , 22 ]. Moreover, recombinant consensus CPB2 protein was employed as an antigen to produce antibodies and was subsequently used for the development of an Enzyme-linked Immunosorbent Assay (ELISA) for the detection and quantification of the toxin in the piglet’s intestinal material [ 6 , 7 , 9 , 13 , 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…CPB2 is an accessory toxin produced by C. perfrignens associated with porcine, equine, and bovine enteritis. While the structure of CPB2 and the identification of residues responsible for its antigenicity and association with the membrane of intestinal epithelial cells are under study [ 67 ], CPB2 has been reported as a pore-forming toxin. Its action mechanism involves forming cation-selective channels approximately 1.4 nm in diameter in lipid bilayers, leading to altered ion flux and increased intestinal permeability [ 34 ].…”
Section: Formation Of Poresmentioning
confidence: 99%